Architecturing of Metal‐Based Composites with Concurrent Nanostructuring: A New Paradigm of Materials Design1. Issue 5 (6th December 2012) - Bouaziz, Olivier; Kim, Hyong Seop; Estrin, Yuri
Abstract Over the past decades severe plastic deformation (SPD) techniques advanced to one of the most potent ways of producing bulk ultrafine grained materials. The main advantage of SPD is the ultra‐high strength they can deliver. While the improvement of the strength there is a limit to what is achievable SPD when they are applied to individual materials especially for strain‐hardening and ductility. Therefore a new application of SPD processes in manufacturing of architecture hybrid materials with simultaneous nanostructuring is investigated experimentally and theoretically.